"EPIDEMIOLOGICAL SURVEILLANCE AND RESISTANCEPROFILING OF MULTIDRUG-RESISTANT BACTERIALISOLATES FROM PEDIATRIC PATIENTS: INSIGHTS FROM ATERTIARY CARE CENTER IN NORTHERN INDIA" - Mohit Kumar; Soumya Singh; Bhavna Bhadauria; Muzziburahaman; Anurag Trivedi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: The rise of antimicrobial resistance presents a significant global challenge for healthcare professionals. Infections resulting from multidrug-resistant organisms (MDROs) pose a considerable threat within Paediatric Intensive Care Units (PICUs). Aim: The current study investigates aims to evaluate the impact of antimicrobial agent resistance in hospital isolates from pediatric patients and to examine the resistance patterns exhibited by MDROs. Materials and Methods: This research involved clinical specimens collected from pediatric patients, both in outpatient and inpatient settings. The samples were developed on blood agar, chocolate agar, and MacConkey agar, with urine cultures being specifically carried out on CLED agar. Bacterial isolates were identified through conventional biochemical testing, and antibiotic susceptibility was evaluated following the 2019 CLSI guidelines using the Kirby-Bauer disk diffusion method. Findings: The overall total is 256 clinical samples were analyzed, leading to the identification of 100 bacterial isolates, which accounts for 39.07% of the samples. The predominant source of these isolates was urine, contributing 65 samples, followed by blood with 22, exudates with 9, and respiratory samples with 4. Among the identified isolates, 22 were classified as multidrug-resistant organisms (MDROs), with 14 originating from urine, 5 from blood, 2 from exudates, and 1 from respiratory samples. The most frequently identified MDROs included E. coli (54%), Klebsiella spp. (36%), and Enterococcus spp. (0.9%). In terms of antibiotic sensitivity for Gram-negative bacteria, polymyxin-B exhibited the highest efficacy at 100%, followed closely by imipenem at 98% and meropenem at 90%. For Gram positive bacteria, the most potent antibiotics were linezolid (100%), vancomycin (97%), and teicoplanin (94%). Conclusion: This investigation reveals the prominent prevalence of multi drug resistant (MDR) pathogens within the pediatric age group. The primary multidrug-resistant organisms (MDROs) identified included E. coli, Klebsiella species, and Enterococcus species, which were mainly sourced from urine culture samples.